Mitochondrial uncoupling and remodelling during caloric restriction: Implications for oxidative stress and aging - Estery, Carmen M (University of Ottawa (Canada), 2009)
The 'uncoupling to survive' theory suggests that mitochondrial uncoupling protects cells from reactive oxygen species (ROS), thereby slowing aging. Caloric restriction (CR) mitigates aging; mechanisms may involve mitochondrial remodelling such that ROS production is decreased. It is unclear how uncoupling protein 3 (UCP3) in skeletal muscle is involved. Objective: To characterize effects of short-term 40% CR in wildtype (Wt) and UCP3 transgenic (UCP3 Tg) mice that possess uncoupled mitochondria. Hypothesis: In an uncoupled system, CR provides no further ROS protection. Approaches: Muscle mitochondrial and whole body assessments of UCP3's contribution to uncoupling and oxidative stress. Results: UCP3 Tg mice had lower body (P<0.001) and muscle weight (P<0.01), increased energy expenditure (P=0.12), similar body composition, increased proton leak (P<0.05), and decreased ROS production (P<0.05). In Wt mice, 1 mo CR mitigated ROS production (P<0.05), increased proton leak (P<0.05), decreased oxidative capacity (P<0.01), and increased UCP3 (P<0.05) protein levels. Such changes were not observed in UCP3 Tg mice. Overall, findings indicate that uncoupling in muscle does not reflect a pre-adaptation to CR. Rather, uncoupling delays the adaptive mitochondrial remodelling normally induced by short-term CR.
Keywords: Chemistry, Biochemistry.